Family bargaining and taxes: a prolegomenon to the analysis of joint taxation - Robert A. Pollak (Institute for the Study of Labor (IZA), 2007)
Does joint taxation disadvantage women? To answer that question, this paper begins by reviewing unitary and bargaining models of intrafamily allocation, and then discusses the determinants of bargaining power in a world without taxes. It argues that wage rates rather than earnings are determinants of bargaining power, and then argues that productivity in household production is also a source of bargaining power. In the absence of human capital effects, joint taxation does not appear to disadvantage women in either divorce threat or separate spheres bargaining. Hence, the claim that joint taxation disadvantages women, if it is correct, depends on effects that operate through the incentives to accumulate human capital. But a satisfactory analysis of the effects of taxation on human capital awaits the further development of dynamic models of family bargaining.
Keywords: 330; Joint taxation; family bargaining; household production; Familienbesteuerung; Geschlechterdiskriminierung; Haushaltsökonomik; Verhandlungsmacht; Familienökonomik; Theorie